Retrofitting options for wastewater networks to achieve climate change reduction targets. (15th May 2018) - Velasquez-Orta, Sharon B.; Heidrich, Oliver; Black, Ken; Graham, David
Graphical abstract: Highlights: Energy use and CO2 emitted across a large wastewater network was quantified. Comparisons of energy and CO2 from pumping vs biological treatment were made. Biological treatment demands the most energy and emits the greatest CO2 . Activated sludge plants use more energy and emit more CO2 than biofilters. Retrofitting to include biofilters will make wastewater networks more sustainable. Abstract: An alternate approach to urban and regional planning is presented that considers the wastewater infrastructure from an energy consumption and carbon production perspective. The existing wastewater infrastructure from four counties in North East England region is investigated, which includes energy and carbon dioxide (CO2 ) data from 87 wastewater treatment plants (WWTPs) (16 activated sludge (AS) and 71 biofilter (BF) plants) and 196 pump stations across the region. This study provides a rigorous and novel way of justifying new investments for retrofitting treatment technologies to the wastewater network. Mass and energy balances are performed across the network utilising a spread-sheet based model. Overall, energy use and CO2 emissions are greatest in biological wastewater treatment (relative to other network elements) with estimated median levels of 0.37 kWh/m 3 and 0.40 kg-CO2 /m 3, respectively, per waste volume processed. However, energy-use and CO2 emissions differed according to treatment technology with AS plants using significantly more energy (median = 0.4 kWh/m 3 ) and producing more CO2 (median = 0.4 kg-CO2 /m 3 ) than BF plants (medians: 0.2 kWh/m 3 and 0.3 kg-CO2 /m 3, respectively). Hence, directed interventions within WWTPs themselves will have the greatest positive influence on energy use and CO2 emissions. Given water companies are often locked-in with their infrastructure, retrofitting existing treatment networks is strongly suggested. For example, adding BF pre-treatment to existing AS plants will reduce energy use, whereas anaerobic or photosynthetic technologies may be useful for reducing energy and CO2 emissions in new-builds. This study confirms energy and carbon dioxide inefficiencies exist in modern wastewater networks, but uniquely identifies targeted actions to reduce inefficiencies, especially retrofitting existing WWTPs to reduce CO2 emitted and energy used in the wastewater infrastructure to make major advances towards achieving climate change reduction targets.